Current Trends and Future Prospects of Artificial Intelligence in Transforming Radiology - Mahedi, Rezwan Ahmed; Iqbal, Hrishik; Azmee, Raiyan; Azmee, Marzan; Jakir, Fatiha; Nishan, Mufassir Ahmad; Uddin, Mohammed Burhan; Afrin, Sadia (Utan Kayu Publishing, 2024)
Artificial intelligence (AI) has rapidly transformed numerous industries, including medicine, with radiography standing to benefit significantly from its capabilities. AI enhances diagnostic accuracy, reduces errors, and improves patient care by leveraging large datasets from digital radiographs commonly used in medical and dental practices. Despite these advantages, the impact of AI on image acquisition and radiographer workflows remains underexplored in radiography literature. This review aims to evaluate the effects of AI on radiographic practices, address regulatory challenges, and explore its integration into educational frameworks for radiologists and radiographers. It highlights AI's role in automating tasks, enhancing diagnostic precision, and improving clinical decision-making. A systematic literature search was conducted using PubMed and Google Scholar up to December 2024, with terms including